Sunlight on the snow leopard - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series., 2022)
The magic tree house is back with a message from Morgan le Fay telling Jack and Annie to seek out "The Gray Ghost" and listen to her story, and immediately they are whisked away to Nepal where they meet Tenzin, a climber who has recently lost his family, and who takes them up the mountain to meet a snow leopard and renew himself.